Hypersonic inviscid flow - Hayes, Wallace D. (Dover books on physics., 2004)
This treatment of the branch of fluid mechanics known as hypersonic inviscid flow presents a unified, self-contained view of nonequilibrium effects, body geometries, and similitudes available in hypersonic flow and thin shock layer. Appropriate for graduate-level courses in hypersonic flow theory and courses dealing with compressible flow. 1966 edition.